An evaluation of EFL program objectives at tertiary level in Iran - Karim Sadeghi (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study was an attempt to evaluate, firstly, whether the objectives specified by the Ministry of Science, Research and Technology (MSRT) of Iran for a BA degree in English Language and Literature (ELL) are relevant and appropriate, and secondly, whether these intended objectives match those reported to have been achieved by students and graduates. For this purpose, 178 participants from Urmia University took part in the study, and different questionnaires were developed and used for collecting relevant data. The study employed both quantitative and qualitative methods for data collection and analysis through the use of both open-ended and closed questionnaire items. The results revealed that the current objectives for education leading to a BA in ELL are regarded as unacceptable. Furthermore, what is expected does not exactly match what is actually achieved. The findings showed that significant changes must be made to English language education in Iran’s university sector by revising the current curriculum to place greater emphasis on the needs of the society and students. Additional findings and implications are also discussed.